2014
DOI: 10.1021/nn505176a
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Local Electrostatic Effects with Scanning Probe Microscopy: Implications for Piezoresponse Force Microscopy and Triboelectricity

Abstract: The implementation of contact mode Kelvin probe force microscopy (cKPFM) utilizes the electrostatic interactions between tip and sample when the tip and sample are in contact with each other. Surprisingly, the electrostatic forces in contact are large enough to be measured even with tips as stiff as 4.5 N/m. As for traditional noncontact KPFM, the signal depends strongly on electrical properties of the sample, such as the dielectric constant, and the tip properties, such as the stiffness. Since the tip is in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
170
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 130 publications
(176 citation statements)
references
References 31 publications
3
170
0
Order By: Relevance
“…99,335,346 A straightforward way to separate these contributions is to consider potentialdependence of forces acting on the junction in contact, i.e. to consider the so-called on-field observables.…”
Section: Vib Contact Kelvin Probe Force Microscopymentioning
confidence: 99%
See 2 more Smart Citations
“…99,335,346 A straightforward way to separate these contributions is to consider potentialdependence of forces acting on the junction in contact, i.e. to consider the so-called on-field observables.…”
Section: Vib Contact Kelvin Probe Force Microscopymentioning
confidence: 99%
“…The more complex qualitative method to measure the DC-bias-dependence of the PFM signal was introduced through a technique called contact KPFM (cKPFM 346 ). The disadvantage of just measuring the hysteresis loops in a spectroscopic manner as described above is that the fact that the remnant state which is altered by the DC voltage is only probed at 0Vdc.…”
Section: Vib Contact Kelvin Probe Force Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Such local and non-local electrostatic effects can arise from the various electrical interactions between the AFM tip/cantilever and sample surface, such as the capacitive interaction, [80,81] the CPD, [79,82] the application of an external voltage to the entire sample, and the corresponding injected charges on the sample surface. [83][84][85] Hong et al reported a significant influence of the electrostatic effect on piezoresponse hysteresis loop measurements. [81] A piezoresponse hysteresis loop is generally measured using a triangular waveform, which can be of two kinds, referred to as continuous and pulsed dc modes, as shown in Figs.…”
Section: Fig 3 Local and Non-local Electrostatic Effects In The Afmmentioning
confidence: 99%
“…KPFM conducted in contact mode allows to differentiate electromechanical and electrostatic phenomena and provides higher lateral resolution than non-contact mode KPFM (Balke et al, 2014).…”
Section: Electrostatic Interactionsmentioning
confidence: 99%